Didactic Principles of Teaching Tatar Language as Non-Native - SHAKIROVA, G.R; KHARISOV, F.F; KUSAINOV, A.K (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Modern educational culture has been undergoing serious changes. The Federal state educational standard sets new requirements for teaching all subjects, including languages, namely, the implementation of a system-activity approach in the organization of the educational process, which provides for the activities of students to form universal educational actions designed to ensure a high level of language training. The article is of practical significance and can be used by specialists in the field of linguodidactics and teachers in the process of teaching the Tatar language, as a result of which the communicative abilities of students will be significantly higher and stronger. RESUMEN La cultura educativa moderna ha experimentado serios cambios. El estándar educativo estatal federal establece nuevos requisitos para la enseñanza de todas las materias, incluidos los idiomas, a saber, la implementación de un enfoque de actividad del sistema en la organización del proceso educativo, que prevé que las actividades de los estudiantes formen acciones educativas universales diseñadas para garantizar alto nivel de formación lingüística. El artículo es de importancia práctica y puede ser utilizado por especialistas en el campo de la lingüística y los docentes en el proceso de enseñanza del idioma tártaro, como resultado de lo cual las habilidades comunicativas de los estudiantes serán significativamente mayores y más fuertes.